THE ISLAMIZATION OF ALFRED ADLER’S CONCEPT OF THE INFERIORITY COMPLEX: INTEGRATING THE ISLAMIC WORLDVIEW INTO MODERN PSYCHOLOGICAL THEORY - Khakim, Usmanul; Mahfud, Musthofa Ali (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
The concept of the inferiority complex developed by Alfred Adler has been widely applied in contemporary psychology to explain conditions such as depression, anxiety, and personality disorders. However, existing solutions tend to be secular, overlooking the spiritual dimension and relying on partial approaches such as tabula rasa, heredity, or nativism, thereby lacking a holistic perspective. This study aims to explore and Islamize Adler’s concept of the inferiority complex by drawing on Adler’s works, Islamic sources, particularly the Qur’an and Hadith, as well as insights from modern Western psychologists and Muslim scholars. Employing a qualitative methodology with a library research approach, the study analyzes primary and secondary texts to identify secular elements in Adler’s theory and integrate them with Islamic principles. The findings show that while Adler’s concept is useful for understanding human psychology, it is rooted in a secular Western paradigm that emphasizes human autonomy and neglects dependence on God. Using Syed Muhammad Naquib al-Attas’s framework of Islamization of knowledge, the concept is reconstructed in three stages: De-Westernization (removing secular elements), integration (embedding values such as tawḥīd, fiṭrah, muḥāsabah, tawakkul, shukr, qanā‘ah, and ukhuwah Islāmiyyah), and Islamization (a comprehensive reconstruction aligned with the tawhidic worldview). The resulting framework is holistic, uniting psychological, social, and spiritual dimensions. Within this perspective, the inferiority complex not only addresses mental health but also strengthens faith, cultivates virtuous character, and affirms humanity’s role as God’s vicegerent (khalīfah). Thus, this study contributes to the development of modern Islamic psychology that is both relevant to Muslim communities and oriented toward worldly well-being and eternal happiness.